Nitrogen-doped carbon-coated lithium manganese iron phosphate as well as preparation method and application thereof
By using nitrogen-doped carbon coating technology on lithium manganese iron phosphate materials, using organic dispersants to form a protective film and achieving nitrogen doping and carbon coating during high-temperature sintering, the problems of low conductivity and insufficient stability of lithium manganese iron phosphate materials are solved, and the electrochemical performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411854652.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The electronic conductivity of lithium manganese iron phosphate material is low and its stability is insufficient during carbon coating modification, resulting in the carbon layer being easily shedded or cracked during battery charging and discharging.
The preparation method of nitrogen-doped carbon-coated lithium manganese iron phosphate is adopted. By adding specific types of organic dispersants, such as chitosan, polyvinylpyrrolidone or polyethyleneimine, to the surface of lithium manganese iron phosphate particles, a protective film is formed and nitrogen doping and carbon coating is achieved during high temperature sintering.
It improves the conductivity and stability of lithium manganese iron phosphate material, enhances the affinity between the material and the carbon layer, reduces the internal impedance of the battery, and improves the electrochemical performance.
Smart Images

Figure BDA0005192521280000101 
Figure BDA0005192521280000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a nitrogen-doped carbon-coated lithium manganese iron phosphate and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have a high energy density, which means that they can store more energy at the same weight or volume, making them very suitable for use in devices that require long-term power supply but are limited by weight or volume, such as smartphones, laptops, and electric vehicles. The positive electrode material of lithium-ion batteries is an indispensable functional structural unit of the battery and directly affects the performance of lithium-ion batteries.
[0003] As a new type of positive electrode material for lithium-ion batteries, lithium manganese iron phosphate (LMFP) introduces manganese elements compared to traditional lithium iron phosphate (LFP), which can provide a higher voltage platform (about 4.1V), thereby improving the energy density of the battery. However, the electronic conductivity of lithium manganese iron phosphate is two orders of magnitude lower than that of lithium iron phosphate, which will lead to slower electron transfer and affect the charge and discharge rate and overall electrochemical performance. Therefore, it is usually used to improve the conductivity of lithium manganese iron phosphate by means of surface element doping or surface carbon coating.
[0004] The carbon coating has good conductivity and can provide a fast transmission channel for electrons, which helps to improve the electron transmission efficiency inside the material, reduce polarization during battery charging and discharging, and improve the overall performance of the battery. However, the affinity between lithium manganese iron phosphate material and the carbon layer is poor, which may cause the carbon layer to be unable to adhere tightly to the surface of the lithium manganese iron phosphate material during long-term cycles. As a result, during the battery charging and discharging process, the carbon layer is prone to fall off or cracks due to volume expansion or contraction.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate, which is used to improve the defects of low electronic conductivity and insufficient stability of existing lithium manganese iron phosphate positive electrode materials when carbon coating modification is adopted.
[0007] The second object of the present invention is to provide a lithium manganese iron phosphate having electrochemical properties such as strong cycle stability and good conductivity.
[0008] A third object of the present invention is to provide a lithium ion battery.
[0009] A fourth object of the present invention is to provide an electrical device.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] A method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate comprises the following steps:
[0012] (1) mixing and grinding a solution containing a phosphorus source, a lithium source, an iron source, and a manganese source to obtain a first material;
[0013] (2) adding a dispersant to the first material, mixing and grinding, to obtain a second material;
[0014] (3) spray drying, sintering and crushing the second material in sequence to obtain a lithium manganese iron phosphate positive electrode material;
[0015] Wherein, the dispersant includes at least one of chitosan, polyvinyl pyrrolidone or polyethylene imine.
[0016] A lithium manganese iron phosphate is prepared according to the preparation method of the nitrogen-doped carbon-coated lithium manganese iron phosphate.
[0017] A lithium-ion battery comprises the lithium iron manganese phosphate.
[0018] An electrical device comprises the lithium-ion battery.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention provides a preparation method of lithium manganese iron phosphate with both nitrogen doping and carbon coating modification modes, by introducing a specific type of organic dispersant: (1) the dispersant is adsorbed on the surface of lithium manganese iron phosphate particles and forms a protective film to prevent direct contact between particles and avoid agglomeration; at the same time, the introduction of the dispersant reduces the viscosity of the slurry during the grinding process, plays a role in improving the dispersibility, and makes the particles more uniform during the spray granulation process; (2) the dispersant acts as a carbon source and a nitrogen source, so that the precursor is nitrogen doped and carbon coated at the same time after high-temperature sintering, effectively improving the conductivity and stability of the lithium manganese iron phosphate material and enhancing its electrochemical performance; specifically, the nitrogen Atoms create defects and extra electronic states in the carbon lattice through CN bonds, increasing the carrier concentration and electron mobility of the carbon layer, making electron transmission smoother, reducing impedance, and improving the affinity between the lithium manganese iron phosphate material and the carbon layer, thereby achieving the purpose of improving electrical properties; (3) The dispersant adjusts the charge distribution on the surface of the lithium iron phosphate particles to generate electrostatic repulsion between the particles, thereby enhancing the dispersion stability; (4) By adding an organic dispersant before the second grinding, the solid content of the slurry can be greatly increased, thereby effectively shortening the time required for grinding, increasing the production volume per unit time, and achieving the effect of improving production efficiency and reducing energy consumption, thereby reducing production costs. DETAILED DESCRIPTION
[0021] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. In addition, the terms "1", "2", "first" etc. are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0022] A first aspect of the present invention is to provide a method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate.
[0023] In the present invention, lithium iron manganese phosphate is modified by nitrogen doping and carbon coating. Among them, lithium iron manganese phosphate is modified by carbon coating to achieve better conductivity and provide a channel for rapid transmission of electrons. At the same time, nitrogen-containing dispersants are doped between lithium iron manganese phosphate particles to improve the affinity between the lithium iron manganese phosphate material and the carbon layer. The introduction of nitrogen atoms will produce defects and additional electronic states in the carbon lattice, increase the carrier concentration and electron mobility of the carbon layer, make electron transmission smoother, reduce impedance, and thus improve the overall conductivity of the material, thereby achieving an overall improvement in electrochemical performance.
[0024] (1) A solution containing a phosphorus source, a lithium source, an iron source and a manganese source is mixed and ground to obtain a first material.
[0025] As a preferred embodiment, the phosphorus source includes at least one of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
[0026] As a preferred embodiment, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium acetate.
[0027] As a preferred embodiment, the iron source includes at least one of ferrous sulfate, ferrous oxalate, ferric phosphate, ferrous phosphate, ferrous oxide or ferrosiric oxide.
[0028] As a preferred embodiment, the manganese source includes at least one of manganese carbonate, manganese acetate, manganese trioxide, manganese oxalate, manganese dioxide and manganese tetraoxide.
[0029] It is understandable that each raw material source of the present invention can adopt any one of the above-mentioned ones, or any combination of multiple ones; as some typical but non-limiting examples, the phosphorus source is a combination of diammonium phosphate and phosphoric acid, and the lithium source is lithium carbonate, or a combination of lithium hydroxide and lithium acetate.
[0030] As a preferred embodiment, in the first material, the molar ratio of phosphorus, lithium, iron and manganese is 1:1:(0.3-0.7):(0.3-0.7); in some optional embodiments, the molar ratio includes but is not limited to 1:1:0.3:0.3, 1:1:0.3:0.7, 1:1:0.4:0.5, 1:1:0.4:0.7, 1:1:0.5:0.4, 1:1:0.6:0.7, etc. In the present invention, it is necessary to macroscopically limit the amount of each element in the unlimited raw material source to ensure that the precursor quality is stable and free of impurities, and finally obtain a lithium manganese iron phosphate positive electrode material with excellent electrochemical performance.
[0031] As a preferred embodiment, the solid content of the solution is 40% to 60%, and the solvent is deionized water. In some optional embodiments, the solid content includes but is not limited to any one of 40%, 45%, 50%, 55%, and 60%, or a numerical range consisting of any two of them; it is understandable that those skilled in the art can adaptively adjust the solid content of the solution within the above range based on the dispersibility and particle size of the selected raw materials; in some optional cases, before grinding, methods such as oscillation, stirring, centrifugation, and ultrasound can be used to assist in obtaining a uniformly dispersed solution system.
[0032] As a preferred embodiment, the grinding in step (1) and step (2) is performed by ball milling, vibration milling, etc. It is understood that mixing the reaction raw materials by grinding can not only play the role of mixing the reaction raw materials evenly, but also play the role of refining the particle size of the raw materials, thereby facilitating the uniformity of the lithium manganese iron phosphate particles obtained by subsequent sintering. In some more preferred embodiments, the grinding time is 0.5h to 2h.
[0033] As a preferred embodiment, in step (1), after the grinding, the particle size of the first material is 0.8 μm to 1.8 μm.
[0034] (2) adding a dispersant to the first material, mixing and grinding, and obtaining a second material, wherein the dispersant comprises at least one of chitosan, polyvinyl pyrrolidone or polyethyleneimine.
[0035] As a preferred embodiment, the chitosan (C6H 13 NO5) nThe molecular weight is 5000-10000 (unit: g / mol).
[0036] As a preferred embodiment, the polyvinyl pyrrolidone (C6H9NO) n The molecular weight is 1000-10000 (unit: g / mol).
[0037] As a preferred embodiment, the polyethyleneimine (C2H5N) n The molecular weight is 1000-10000 (unit: g / mol).
[0038] As a preferred embodiment, the amount of the dispersant added is 10% to 20% of the sum of the phosphorus source, the lithium source, the iron source and the manganese source, measured by mass. It can also be understood that the amount of the dispersant added is 10% to 20% of the mass of the first material excluding the solvent, including but not limited to any one of 10%, 12%, 15%, 18%, 20% or a numerical range consisting of any two of them.
[0039] As a preferred embodiment, in this step, the grinding time is 2 hours to 5 hours. At the same time, based on the grinding, in some preferred embodiments, the median particle size of the second material is 0.3 μm to 0.4 μm.
[0040] (3) spray drying, sintering and crushing the second material in sequence to obtain a lithium manganese iron phosphate positive electrode material.
[0041] As a preferred embodiment, the inlet air temperature of the spray drying is 200°C to 260°C, the outlet air temperature is 85°C to 100°C, and the frequency of the atomizer is 30Hz to 50Hz. In some optional embodiments, the inlet air temperature of the spray drying includes but is not limited to any one of 200, 210, 220, 230, 240, 250, 260 (°C) or a numerical range consisting of any two thereof, and the outlet air temperature includes but is not limited to any one of 85, 88, 90, 92, 95, 98, 100 (°C) or a numerical range consisting of any two thereof.
[0042] As a preferred embodiment, the sintering temperature is 600°C to 790°C, and the sintering holding time is 7h to 12h; in some optional embodiments, the sintering temperature includes but is not limited to any one of 600, 620, 640, 650, 660, 680, 700, 720, 740, 750, 760, 780, 790 (°C) or a numerical range formed by any two of them, and the sintering holding time includes but is not limited to any one of 7, 8, 9, 10, 11, 12 (h) or a numerical range formed by any two of them.
[0043] In the present invention, the sintering treatment temperature and treatment time are limited to the above ranges respectively. On the one hand, when the temperature is too low, the molecular activity and molecular thermal motion are not obvious enough, so they can only be compensated by the sintering time, which easily leads to a waste of time and energy costs; on the other hand, the molecular activity and molecular thermal motion will be too high, and overburning of lithium manganese iron phosphate may occur. Within the above range, sintering can obtain lithium manganese iron phosphate with appropriate compaction density and electrochemical properties.
[0044] As a preferred embodiment, the sintering heating rate is 2°C / min to 10°C / min, including but not limited to any one of 2, 3, 4, 5, 6, 7, 8, 9, 10 (°C / min) or a numerical range consisting of any two of them.
[0045] As a preferred embodiment, the sintering is performed under an inert atmosphere; the inert atmosphere includes but is not limited to nitrogen, helium, neon or argon.
[0046] As a preferred embodiment, the crushing includes dry grinding, mechanical crushing, air flow crushing, etc. After the crushing, it can optionally include screening to obtain lithium manganese iron phosphate material with suitable particle size.
[0047] As a preferred embodiment, after the crushing, the median particle size of the lithium iron manganese phosphate is 0.7 μm to 1.4 μm.
[0048] The second aspect of the present invention is to provide lithium manganese iron phosphate prepared by the preparation method of nitrogen-doped carbon-coated lithium manganese iron phosphate as described in the first aspect.
[0049] A third aspect of the present invention is to provide a lithium ion battery.
[0050] The lithium-ion battery includes the lithium iron manganese phosphate as described in the second aspect. It is understandable that the lithium iron manganese phosphate is the active ingredient of the positive electrode of the lithium-ion battery, or one of the active ingredients of the positive electrode of the lithium-ion battery; the positive electrode of the lithium-ion battery may also include structural elements or functional components such as a conductive agent, a binder, and a current collector; the lithium-ion battery also includes a negative electrode, an electrolyte, a diaphragm, and other necessary or non-essential functional elements or packaging components, etc., which can be arbitrarily selected and combined by those skilled in the art; when the lithium iron manganese phosphate described in the present invention is included in the lithium-ion battery, it can be regarded as an embodiment of the present invention.
[0051] As a preferred embodiment, the active ingredients of the negative electrode include but are not limited to natural graphite, artificial graphite, silicon-carbon composite materials, soft carbon, hard carbon, lithium titanate, metallic lithium, etc.; the diaphragm includes but is not limited to polyethylene diaphragm, polypropylene diaphragm, polyimide diaphragm, etc.; the electrolyte includes lithium salt and organic solvent, wherein the lithium salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, etc., and the organic solvent includes any cyclic carbonate or chain acid ester, etc.
[0052] A fourth aspect of the present invention is to provide an electrical device.
[0053] The electrical equipment includes the lithium-ion battery as described in the third aspect. The electrical equipment can be any equipment or device that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc. When including the lithium-ion battery, any electrical equipment equipped with the lithium-ion battery can belong to an embodiment of the present invention.
[0054] Example 1
[0055] (1) Lithium carbonate, iron phosphate, manganese dioxide and phosphoric acid were weighed so that the molar ratio of Li:Fe:Mn:P was 1:0.5:0.5:1, deionized water was added to prepare a solution with a solid content of 46%, and the mixture was ground for 1 h to obtain slurry A.
[0056] (2) adding an organic dispersant according to 15% of the total mass of the non-aqueous raw materials added; the dispersant used in this embodiment is industrial grade chitosan, which has the following specifications or properties: molecular weight 7500, deacetylation degree ≥85%, particle size ≥80 mesh, heavy metal ≤10%, moisture ≤10%; after adding the dispersant, the solid content is 50%, ball milling is performed for 3 hours, and the slurry D50 is ground to 0.3 μm; the slurry is further filtered through a 325 mesh screen to obtain slurry B.
[0057] (3) The slurry B was spray dried with a spray inlet temperature of 220°C, an outlet temperature of 88°C, and a compressed air pressure of 0.4 MPa; then moved to a tubular atmosphere furnace, and heated to 780°C at a rate of 5°C / min and calcined for 10 h under the protection of a circulating argon atmosphere; after natural cooling, the slurry was crushed to a D50 of 1.0 μm to obtain the nitrogen-doped carbon-coated lithium manganese iron phosphate material in this embodiment.
[0058] Example 2
[0059] It is basically the same as Example 1, except that chitosan is replaced by industrial grade polyvinyl pyrrolidone, and has the following specifications or properties: average molecular weight of 6000, K value of 15, main content ≥97%, pH of 3-5, nitrogen content of 11.5-12.8%, and heavy metal ≤10%.
[0060] Example 3
[0061] It is basically the same as Example 1, except that chitosan is replaced by industrial grade polyethyleneimine, and has the following specifications or properties: average molecular weight of 6000, main content ≥95%, impurity content ≤0.5%, heavy metal content ≤10%, and moisture content <5%.
[0062] Example 4
[0063] The process is basically the same as Example 1, except that the raw materials in step (1) are replaced by lithium hydroxide, ferrous oxalate, manganese oxalate and lithium dihydrogen phosphate.
[0064] Example 5
[0065] It is basically the same as Example 1, except that the sintering in step (3) is replaced by heating to 600° C. at a rate of 3° C. / min and calcining for 12 h.
[0066] Example 6
[0067] The method is basically the same as Example 1, except that the sintering in step (3) is replaced by heating to 770° C. at a rate of 10° C. / min and calcining for 7 h.
[0068] Comparative Example
[0069] The method is basically the same as Example 1, except that the addition of chitosan in step (2) is omitted.
[0070] Test example
[0071] (1) The compaction density of the lithium manganese iron phosphate prepared in each embodiment and comparative example was tested by a powder tap density meter.
[0072] (2) The resistivity of the lithium manganese iron phosphate prepared in each embodiment and comparative example was tested by a powder resistivity tester.
[0073] (3) The lithium iron manganese phosphate prepared in each embodiment and comparative example is formulated to obtain a corresponding lithium ion battery. First, the lithium iron manganese phosphate prepared in the above embodiments and comparative examples is mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 96:1.5:2.5 by volume with N-methylpyrrolidone to obtain a positive electrode slurry, which is then coated on aluminum foil and baked and cut into pieces to obtain a positive electrode. Metal lithium is used as the negative electrode, a polyethylene microporous membrane is used as the separator, EC:EMC (mass ratio 3:7) is used as the solvent, and 1.6M lithium hexafluorophosphate is added as the electrolyte to prepare a CR2032 coin battery for testing.
[0074] Each battery was tested by using the LANDBT1-10 test system as a constant current charge and discharge device, the test temperature was 25°C, the voltage was set to 2.5V to 4.5V, and the discharge specific capacity and first-efficiency performance data of each battery were obtained. The test result table of this test example is shown in Table 1.
[0075] Table 1
[0076]
[0077]
[0078] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate, characterized in that: The steps include: (1) mixing and grinding a solution containing a phosphorus source, a lithium source, an iron source, and a manganese source to obtain a first material; (2) adding a dispersant to the first material, mixing and grinding, to obtain a second material; (3) spray drying, sintering and crushing the second material in sequence to obtain a lithium manganese iron phosphate positive electrode material; Wherein, the dispersant includes at least one of chitosan, polyvinyl pyrrolidone or polyethylene imine.
2. The method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to claim 1, characterized in that: The phosphorus source includes at least one of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate; And / or, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium acetate; And / or, the iron source includes at least one of ferrous sulfate, ferrous oxalate, ferric phosphate, ferrous phosphate, ferrous oxide or ferrosoferric oxide; And / or, the manganese source includes at least one of manganese carbonate, manganese acetate, manganese trioxide, manganese oxalate, manganese dioxide and manganese tetraoxide.
3. The method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to claim 1, characterized in that: In the first material, the molar ratio of phosphorus, lithium, iron and manganese is 1:1:(0.3-0.7):(0.3-0.7).
4. The method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to claim 1, characterized in that: The particle size of the first material is 0.8 μm to 1.8 μm; And / or, the median particle size of the second material is 0.3 μm to 0.4 μm; And / or, the median particle size of the lithium manganese iron phosphate positive electrode material is 0.7 μm to 1.4 μm.
5. The method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to claim 1, characterized in that: The molecular weight of the chitosan is 5000 to 10000; and / or, the molecular weight of the polyvinyl pyrrolidone is 1000 to 10000; And / or, the molecular weight of the polyethyleneimine is 1000-10000.
6. The method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to claim 1, characterized in that: The inlet air temperature of the spray drying is 200°C to 260°C, and the outlet air temperature is 85°C to 100°C.
7. The method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to claim 1, characterized in that: The sintering temperature is 600°C to 790°C, and the sintering holding time is 7h to 12h; Preferably, the heating rate of the sintering is 2°C / min to 10°C / min.
8. Lithium manganese iron phosphate obtained by the method for preparing nitrogen-doped carbon-coated lithium manganese iron phosphate according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: Comprising the lithium manganese iron phosphate as described in claim 8.
10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.
Citation Information
Cited By
High-conductivity lithium manganese iron phosphate positive electrode material and preparation method thereof
CN120483086A
Polyelectrolyte membrane coated lithium manganese iron phosphate positive electrode material and preparation method thereof
CN122068024A